miR-144/451 in hematopoiesis and beyond - Ting Wang; Fan Wu; Duonan Yu (ExRNA)
Abstract MicroRNAs (miRNAs), a class of 18–25 nucleotide (nt) non-coding RNAs, usually inhibit the expression of their target genes. They are transcribed from endogenous genes and are processed for maturation by multiple pathways. miR-144/451, a bicistronic gene locus, encodes miR-144 and miR-451, both of which are highly conserved in evolution. These two miRNAs are on the same primary RNA molecule whose transcription is controlled by multiple nuclear proteins, including GATA1, GATA4, Myc, Oct1, Pax4, FXR, AP1, SMAD3 and SMAD4 depending on tissue types. They are abundant and almost exclusively exist in red blood cells, but low expression of both miR-144 and miR-451 are also detected in non-erythroid lineages. Interestingly, deletion of both miR-144 and miR-451 DNA sequences coding pre-miR-144/451 hairpins in mice leads only mild microcytic anemia but worsen upon a number of stresses including developmental stress, acute blood loss, phenohydrazine-induced hemolysis and precursor depletion by chemotherapeutic drug 5-FU. Such knockout animals older than 15 months also spontaneously develop malignant tumors including B-lymphoma and acute myeloid leukemia, indicating that miR-144/451 is a bona fide tumor-suppressing gene in non-erythroid cells, though its levels are much lower compared to that in red blood cells. Consistent with the findings in animals, disruption of miR-144/451 expression and their abnormal functions are observed in human hematopoietic and non-hematopoietic organs. Moreover, miR-451 is the only miRNA discovered so far whose maturation does not depend on Dicer, an enzyme required by all other miRNAs for maturation. This review focuses on the biogenesis, transcriptional regulation and biological roles of miR-144/451 in erythropoiesis, tumor initiation and other pathological conditions.